THE EFFECT OF VISUAL MEDIA ON STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURE TEXT - Arie Dwiutami; Sumarsih Sumarsih; Rafika Dewi Nasution (Universitas Negeri Medan, 2017)
This study focused on finding out the effect of Visual media on students’ achievement in writing procedure text. This study was conducted in experimental design. The population of this research was the seventh grade students of SMP Negeri 1 Stabat. There are 60 students of seventh grade as sample of the research. This study was conducted by using random sampling. The sample was divided into two groups, experimental group and control group. The experimental group was taught by using Visual media (picture), while the control group was taught by using Video. The instrument of collecting the data was a written test. To obtain the reliability of the test, the researcher used scoring rubrics. The data were analyzed by using t-test formula. The calculation shown that t-observed is higher than t-table (3.52 > 2.00) at the level signivicance (α) 0.05 with the degree of freedom 58 (df = N-2). It means that there was a significant effect of using Visual media on students’ achievement in writing procedure text. So, the null hypothesis (Ho) is rejected and alternative hypothesis (Ha) is accepted.Keywords: Visual Media, Students’ Achievement, Writing Procedure Text